Acute Liver Failure of Indeterminate Etiology: A Comprehensive Systematic Approach by An Expert Committee to Establish Causality. (September 2018) - Ganger, Daniel R.; Rule, Jody; Rakela, Jorge; Bass, Nathan; Reuben, A; Stravitz, R T; Sussman, Norman; Larson, Anne M.; James, Laura; Chiu, Charles; Lee, William M.
Abstract : OBJECTIVES: In the United States, the Acute Liver Failure Study Group (ALFSG) registry lists approximately 11% of cases as of indeterminate etiology (IND‐ALF) as determined by the respective local site principal investigator (PI). Traditionally, IND‐ALF has prompted concern that other viruses or toxins might be implicated. We hypothesized that many IND‐ ALF cases would have an identifiable etiology upon further investigation. Improving the identification process should reduce the number of truly indeterminate cases. METHODS: Specific definitions for each etiology ("etiology‐specific algorithms") were developed by a Causality Adjudication Committee that included six reviewers (each with 20 or more years of experience). Of 2718 patients with ALF, 303 initially deemed IND‐ALF by site PIs underwent committee review guided by the algorithms. Acetaminophen (APAP) protein adducts were measured in sera when available, additional HEV testing was performed, and viral sequences sought by microarray analysis and metagenomic next‐generation sequencing (mNGS). Study sites were asked to provide liver biopsy and/or explant reports and to update serological findings not reported previously. RESULTS: Nearly half (142, 46.9%) of the 303 IND‐ALF cases could be reassigned to a single, defined etiology and rated as highly likely or probable; 11 additional cases, upon review, did not meet ALF criteria. Amongst reassigned etiologies, 45 were previously unrecognized APAP, 34 autoimmune hepatitis (AIH), 24 drug‐induced liver injury (DILI), 13 various viral causes, 12 ischemia, and 14 miscellaneous other etiologies. The remaining 150, deemed true IND‐ALF, represented just 5.5%. CONCLUSIONS: The indeterminate etiology in ALF includes patients with a diagnosis that is discernible after closer examination. Revision of etiologic diagnoses of indeterminate cases using added testing and expert opinion is useful in understanding all aspects of ALF.